Pengaruh Citarasa, Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Rokok Gudang Garam Surya (Studi Kasus pada Konsumen Rokok di Kabupaten Situbondo) - Adhim, Mohammad Fauzil; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract Research on the Influence of Flavor, Product Quality and Brand Image on the Decision to Purchase Gudang Garam Surya Cigarettes (Case Study of Cigarette Consumers in Situbondo Regency) aims to determine and test the factors that influence consumers' decisions to purchase Gudang Garam Surya cigarettes including taste, product quality and image brand. The population of this study consisted of 75 smoker respondents in Situbondo Regency. In this research, a purposive sampling method was used for sampling. Primary data collection in this research used Google forms. The test uses multiple linear regression analysis using the SPSS version 29 application. The further impact of this exploration shows that taste, product quality and brand image simultaneously influence purchasing decisions. Meanwhile, the taste and quality of the product partially influence purchasing decisions, while brand image does not partially influence purchasing decisions. Keywords: Taste, Product Quality, Brand Image, Purchase Decision